Memperkuat Loyalitas Elektronik Melalui Kualitas Layanan Elektronik Dan Nilai Pengalaman Pada Platform Perjalanan Digital - Fongiman, Evelyn Khezya; Utama, Vionisia Efelin; Ardyan, Elia (STIM-LPI Makassar, 2025)
Digital travel platforms have significantly transformed the tourism industry, reshaping consumer behavior and service delivery processes. This study aims to examine the role of e-service quality in influencing cognitive and hedonic experiential value and its impact on e-loyalty in digital travel platforms. Data were collected through structured questionnaires from 66 respondents with prior experience using platforms such as Traveloka, Booking.com, and Tiket.com. Data analysis was conducted using Structural Equation Modeling (SEM) to test the proposed hypotheses. The findings reveal that e-service quality has a positive and significant effect on both cognitive and hedonic experiential value, with cognitive value exerting a stronger influence. Furthermore, cognitive and hedonic experiential values also positively impact e-loyalty, with cognitive value demonstrating a more substantial effect. These results emphasize the importance of experiential value in bridging the relationship between e-service quality and customer loyalty and highlight the necessity for digital travel platforms to provide both functional and emotional experiences to retain customers. This study contributes to the literature by integrating cognitive and hedonic experiential values as key drivers of e-loyalty. Practical implications include the need for digital travel platforms to invest in advanced technologies, such as personalized services and enhanced user interfaces, to optimize the customer experience.